Advanced Strategies for Improving Reading Comprehension Among Open Distance Learners - Onyedibia, Henry Oburu (West African Journal of Open and Flexible Learning, 2015)
Reading is a mandatory requirement for academic success. It is the tool through which knowledge is passed to the faculty of the brain for further usage. This paper is of the opinion that reading as an important part of educational acquisition has been ignored from the angle of less attention paid to essential strategies for boosting reading comprehension It recognizes that the lack of reading enthusiasm among University, college and school students is partly because of the non-knowledge of reading comprehension strategies. Some of the reasons advanced for this fault bordered on the non-inclusion of reading comprehension strategies in the school curriculum; such that the teacher resigns his teaching topic only to reading and answering passage reflected questions. The paper is specifically tailored to address the reading comprehension requirements of the Open Distance Learners (ODL); who would mandatorily do independent reading throughout their programmes of study. The task would be easier if the ODL students and others learn and master these reading comprehension strategies. This paper recommends analogy, reading and reasoning, note taking and notation and others as some of the strategic measures that could boost and equip the ODL students to handle independent reading of selected course materials, especially those at the undergraduate level. The paper concludes that the ODL students could advance their reading comprehension capabilities and success by adopting these advanced strategies.